Extra Cranial Facial Nerve Anatomical Dissection: Fresh Tissue Vs Embalmed Tissue - Fifi Veronica; Rani Septrina; Nandina Oktavina; Nita Novita (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2022)
Anatomical topography of fmelewati gacial nerve is very important as one of basic knowledge for clinical application. Extra cranial facial nerve branches were difficult to identify because of their smaller size and lack of consistent landmark. Dissected skill need experience with various tissue, like fresh and embalmed tissue. This study was aimed to compare the facial nerve anatomical dissection by using fresh tissue and embalmed tissue cadaver. Three fresh tissue cadaver from Forensic Department and three embalmed tissue cadaver (after 2 months preservated by ethanol) from laboratorium Anatomy Department were used to anatomical dissection the topography of extra cranial facial nerve. Incisi line started from midline across the glabella,tip of the nose until philtral groove. Skin flap from midline to lateral until we find the branches of facial nerve. The anatomical dissection of extra cranial facial nerve from 3 embalmed tissue can provide dissected facial nerve and it”s branches. But it is hardly difficult to separate the skin from Superficial Musculo Aponeurotic System (SMAS) compared with fresh cadaveric tissue. Embalmed cadaver and fresh tissue from post mortem body can be used for anatomical dissection study of extra cranial facial nerve. Each different tissue has its own difficulties depends the aim of the dissection study.